It`s dead! Can postbiotics really help performance and recovery? A systematic review - Kerksick, C. M.; Moon, J. M.; Jäger, R. (Nutrients, 2024)
In recent years, postbiotics have increased in popularity, but the potential relevancy of postbiotics for augmenting exercise performance, recovery, and health is underexplored. A systematic literature search of Google Scholar and PubMed databases was performed with the main objective being to identify and summarize the current body of scientific literature on postbiotic supplementation and outcomes related to exercise performance and recovery. Inclusion criteria for this systematic review consisted of peer-reviewed, randomized, double-blind, and placebo-controlled trials, with a population including healthy men or women >18 years of age. Studies required the incorporation of a postbiotic supplementation regimen and an outcome linked to exercise. Search terms included paraprobiotics, Tyndallized probiotics, ghost biotics, heat-killed probiotics, inactivated probiotics, nonviable probiotics, exercise, exercise performance, and recovery. Only investigations written in English were considered. Nine peer-reviewed manuscripts and two published abstracts from conference proceedings were included and reviewed. Supplementation periods ranged from 13 days to 12 weeks. A total of 477 subjects participated in the studies (n = 16-105/study) with reported results spanning a variety of exercise outcomes including exercise performance, recovery of lost strength, body composition, perceptual fatigue and soreness, daily logs of physical conditions, changes in mood states, and biomarkers associated with muscle damage, inflammation, immune modulation, and oxidative stress. Early evidence has provided some indication that postbiotic supplementation may help to support mood, reduce fatigue, and increase the readiness of athletes across several weeks of exercise training. However, more research is needed to further understand how postbiotics may augment health, resiliency, performance, and recovery. Future investigations should include longer supplementation periods spanning a wider variety of competitive athletes and exercising populations.